Waiting times in renal transplant candidates with a history of malignancy: time for a change?. Issue 6 (November 2020) - Bojic, Marija; Watschinger, Clara; Reiter, Thomas; Watschinger, Bruno
Abstract : Purpose of review: With the aging population of kidney transplant candidates, a history of malignancy is an increasingly prevalent finding. Tumors can constitute a contraindication for transplantation or can lead to a delay of acceptance to the waiting-list. Current waiting time guidelines mainly refer to early data collected nearly 30 years ago, when the knowledge on tumors was, by current standards, still limited. Recent findings: Today, cancers can usually be divided into many different biological subtypes, according to histological and molecular subclassification and the availability of genetic testing. A more precise stratification and targeted antitumor therapies have led to better therapy outcomes or even cures from certain malignancies and to a better appreciation of tumor risks for the patient. Summary: Even though transplant patients do have an increased risk for malignancies, it is often overlooked that patients, while on dialysis, are equally prone to develop a tumor. Competing risks (e.g. cardiovascular, mortality risks) through prolonged time on dialysis have to be equally considered, when the decision for acceptance of a patient to the waiting-list is made. Current waiting time suggestions should be critically reconsidered for every patient after a thorough discussion with an oncologist, including new diagnostic and therapeutic strategies, as well as novel risk stratifications.